Teachers' Workplace Victimization, Job Burnout, and Somatic and Posttraumatic Symptoms: A Structural Equation Modeling Examination - Mahira Ghadban; Ruth Berkowitz; Guy Enosh (MDPI AG, 2023)
Teachers' workplace victimization is a serious and concerning problem known to have numerous negative occupational and health outcomes for teachers. Surprisingly, however, the scientific literature has broadly overlooked schools as settings in which serious workplace violence occurs, and it has failed to systematically explore the antecedents and consequences of workplace victimization for teachers. To fill this gap, this study examined the structures of associations of teachers' victimization via threats, verbal violence, and property violence with somatic and posttraumatic symptoms using structural equation modeling. The sample included 366 Arabic and Jewish teachers in Israel. The findings indicate that the teachers who reported victimization and symptoms experienced burnout, whereas the teachers who reported victimization and had no symptoms did not experience burnout. A significant relationship of teachers' personal and professional characteristics with victimization, symptoms, and burnout also emerged. These findings advance our theoretical understanding of the predictors and consequences of violence against teachers in schools. Useful practices to improve teachers' occupational and health outcomes are discussed.